ANALISIS PERBANDINGAN PERTUMBUHAN LABA PERUSAHAAN SEKTOR FOOD & BEVERAGE DI BEI SEBELUM DAN SAAT PANDEMI COVID-19 - Sapna Wadiah; Hapliah; Baiq Dewi Lita Andiana (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2023)
This study aims to compare the profit growth value of food and beverage sub-sector manufacturing companies before the covid-19 pandemic (2018-2019) and profit growth during the covid-19 pandemic (2020-2021). This research was conducted on 23 food and beverage companies that have been listed on the Indonesia Stock Exchange and financial reports for the 2018-2021 period are available on the Indonesia Stock Exchange with descriptive analysis methods. The sampling technique used in this study was saturated sampling technique. The results of the analysis obtained are that out of 23 food and beverage companies 10 out of 17 food companies recorded positive profit growth duri1ng the covid-19 pandemic and 4 out of 7 beverage companies recorded positive profit growth during the covid-19 pandemic. So it can be concluded that the profit growth of food and beverage companies grew more during the covid-19 pandemic than before the covid-19 pandemic.